Elevation of oxidative stress indicators in a pilot study of plasma following traumatic brain injury - Halstrom, A.; MacDonald, E.; Neil, C.; Arendts, G.; Fatovich, D.; Fitzgerald, Melinda (Elsevier, 2017)
Traumatic brain injury (TBI) encompasses a broad range of injury mechanisms and severity. A detailed determination of TBI severity can be a complex challenge, with current clinical tools sometimes insufficient to tailor a clinical response to a spectrum of patient needs. Blood biomarkers of TBI may supplement clinical assessments but currently available biomarkers have limited sensitivity and specificity. While oxidative stress is known to feature in damage mechanisms following TBI, investigation of blood biomarkers of oxidative stress has been limited. This exploratory pilot study of a subset of 18 trauma patients with TBI of varying severity, quantifies circulating concentrations of the structural damage indicators S100b, and myelin basic protein (MBP), and the biomarkers of oxidative stress hydroxynonenal (HNE), malondialdehyde (MDA), carboxy-methyl-lysine (CML), and 8-hydroxy-2'-deoxy-guanosine (8-OHDG). Significant increases in circulating S100b, MBP, and HNE were observed in TBI patient samples compared to 8 uninjured controls, and there was a significant decrease in CML. This small exploratory study supports the current literature on S100b and MBP elevation in TBI, and reveals potential for the use of peripheral oxidative stress markers to assist in determination of TBI severity. Further investigation is required to validate results and confirm trends.